(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This research investigates how concept mapping as a teaching strategy influences cognitive development and academic success in science for middle school students in Ujjain city. Utilizing a quasi-experimental approach, the study included two student groups: one experimental group taught with concept mapping techniques and a control group receiving traditional instruction. Pre-test and post-test evaluations were conducted to assess changes in problem-solving abilities, critical thinking, and academic success in science. The results indicated that the experimental group showed notable improvements in all three areas when compared to the control group. These findings highlight the efficacy of concept mapping in promoting a deeper understanding, improving critical cognitive skills, and enhancing academic performance in science. The study concludes with a recommendation to incorporate concept mapping into science curricula to encourage active learning and critical thinking among students.